Pengaruh Pengembangan Karir, Peran Kepemimpinan, Stres Kerja, dan Motivasi Kerja terhadap Kinerja Karyawan dengan Komitmen Organisasi sebagai “Variabel Antara” - Siti Noor Hidayati (Jurnal Maksipreneur, 2015)
Organizational commitment plays a role in determining the employee’s performance. Such a commitment is affected by many variables, career development,such as leadership role, work stress and work motivation. Effects of career development, leadership role,work stress and work motivation toward the employee’s performance are to be determined, with organizational commitment as the intervening variable. A research has been conducted on 87 employees of Din.TKS Sleman. It can be concluded that, wholly or partially, the effects of leadership role, career development, and work motivation toward employee’s performance are significantly positive; the work stress’ effect is significantly negative. From the four variables, the career development affects dominantly.